IBM Z Integration Guide for Hybrid Cloud - Williams, Nigel; Gamblin, Richard; Jones, Rob (IBM Redbooks, 2020)
Today, organizations are responding to market demands and regulatory requirements faster than ever by extending their applications and data to new digital applications. This drive to deliver new functions at speed has paved the way for a huge growth in cloud-native applications, hosted in both public and private cloud infrastructures. Leading organizations are now exploiting the best of both worlds by combining their traditional enterprise IT with cloud. This hybrid cloud approach places new requirements on the integration architectures needed to bring these two worlds together. One of the largest providers of application logic and data services in enterprises today is IBM Z, making it a critical service provider in a hybrid cloud architecture. The primary goal of this IBM Redpaper publication is to help IT architects choose between the different application integration architectures that can be used for hybrid integration with IBM Z, including REST APIs, messaging, and event streams.